FIXED POINT THEOREM FOR CONTRACTIVE TYPE MAPPING IN DISLOCATED METRIC SPACE - Chouhan, Sarla (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The objective of this paper is to obtain some fixed point theorem for Dislocated metric space for generalized contraction mappings.